The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1038/sj.sc.3101217
|View full text |Cite
|
Sign up to set email alerts
|

Intradural arachnoid cyst associated with thoracic spinal compression fracture: 7-year follow up after surgery

Abstract: Study design: A case report with long-term follow after a surgical procedure. Objectives: To describe a case of intradural arachnoid cyst secondary to a compression fracture in the thoracic spine and to report long-term results after surgical treatment with hemilaminectomy. Setting: Osaka, Japan. Methods: A 68-year-old man who had a traumatic intradural arachnoid cyst following an adjacent compression fracture of T5 underwent surgery. Intraoperatively, after recognition of intradural arachnoid cyst with an ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
0
11
0
4
Order By: Relevance
“…2 Tethering of the spinal cord and arachnoid cyst formation have been associated with previous trauma. 1,16,18,34,37 Arachnoiditis has been found to occur as a result of infection (for example, tuberculosis and malarial infections of the meninges), 9,10,20,24,27 and after cranial aneurysmal subarachnoid hemorrhage, with blood settling in the spinal subarachnoid space and causing delayed arachnoiditis. 3,13,23,39 Ionic intrathecal contrast administration is another known cause of thoracic and lumbar arachnoiditis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Tethering of the spinal cord and arachnoid cyst formation have been associated with previous trauma. 1,16,18,34,37 Arachnoiditis has been found to occur as a result of infection (for example, tuberculosis and malarial infections of the meninges), 9,10,20,24,27 and after cranial aneurysmal subarachnoid hemorrhage, with blood settling in the spinal subarachnoid space and causing delayed arachnoiditis. 3,13,23,39 Ionic intrathecal contrast administration is another known cause of thoracic and lumbar arachnoiditis.…”
Section: Discussionmentioning
confidence: 99%
“…contrast 4,15 and epidural anesthesia, 40 traumatic arachnoiditis, 17,22,25,38 arachnoiditis from subarachnoid hemorrhage, 3,23,39 congenital arachnoid malformations, 6,19,28,32,35 and traumatic 17,37,41 and idiopathic arachnoid cysts. 1,7,13,14,16,21,26,30,34,36,42 Treatment, including nonsurgical and surgical management strategies, has provided mixed results, and follow-up offered in the medical literature has been poor.…”
mentioning
confidence: 99%
“…5,14) Ventriculoperitoneal shunting may be effective in some cases. 1,9) The surgical outcome is unpredictable.…”
Section: Discussionmentioning
confidence: 99%
“…Acquired spinal arachnoid cyst, also called subarachnoid cyst, 16) is a sequela of chronic inflammation in the subarachnoid space. The initiating cause may be trauma, 5,7,14) myelography dye, 10) subarachnoid hemorrhage, 9,17) or infection. 1,12) Acquired spinal arachnoid cyst often occurs at the thoracic level and can arise ventral, lateral, or dorsal to the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Endo et al reported an arachnoid cyst after the operation of an epidural spinal haematoma, whereas Bassiouni et al after a major spinal trauma. Other causes of arachnoid spinal intradural cysts included also traumatic causes such as vertebral fracture [25] or traumatic syringomyelia [2,16].…”
Section: Discussionmentioning
confidence: 99%